The official Ubuntu book - Helmke, Matthew (Prentice Hall, 2012)
Ubuntu is a complete, free operating system that emphasizes ease of use, community, and support while enhancing speed, power, and flexibility. It is designed for everyone from computer novices to experts. This title serves a wide audience: novices who just want to test the waters and give Ubuntu a try, intermediate users, and those who want to take the next step toward becoming power users. It is not intended as a guide to highly technical uses like professional systems administration or programming, although there is some technical material here; the focus is on learning the landscape. New in this edition is deep coverage of the groundbreaking, user-experience-focused Unity desktop, an innovative new style of human--computer interaction that has undergone extensive development and testing to provide powerful, industry-leading usability. In addition, you will Learn how to use and customize Ubuntu for home, small business, school, government, and enterprise environments Learn how to quickly update Ubuntu to new release versions with upgraded applications Find up-to-the-minute troubleshooting advice from Ubuntu users worldwide to get the help you need quickly Learn Ubuntu Server installation and administration, including LVM and RAID implementation The DVD includes the complete Ubuntu Linux operating system for installation on PC platforms. The disk is preconfigured with an outstanding desktop environment for both home and business computing, for novices and advanced users.